COGNITIVE COMPLEXITY REDUCTION IN DECENTRALIZED APPLICATIONS BASED ON BLOCKCHAIN TECHNOLOGY: THE PSYCHOLOGICAL ASPECTS OF USER INSTRUCTION, UNDERSTANDING, AND SELF-EFFICACY (Lex localis - Journal of Local Self-Government, 2025)
Blockchain-based decentralized applications (dApps) face low user adoption owing to high cognitive complexity and psychological barriers, making it difficult for first-time users to understand and operate. This challenge is important because user comprehension, confidence, and perceived ease of use directly influence behavioral acceptance of decentralized systems. Although previous studies have noted usability gaps in blockchain interfaces, few studies have examined whether structured user instructions can reduce cognitive load. This study used a comparative experimental design with 200 participants with no prior dApp experience. User interaction with a centralized application was first assessed, followed by a task-based evaluation of the three dApps. Subsequently, the participants received guided education and practical training. The results show a clear improvement in user readiness: initially, 95% required assistance when using dApps, but post-training, 74% reported higher confidence and comfort levels increased from 20% to 80%. Descriptive statistics and comparative analyses were performed to assess these changes. Overall, the study demonstrates that targeted user education and structured guidance effectively reduce cognitive complexity and enhance acceptance of blockchain-based applications.